Methods for Memorizing the Quran for Higher Education - Marlena, Reni; Cahya, Mutiah; Iskandar, M. Yakub; Yusrial, Yusrial (Ahlussunnah: Journal of Islamic Education, 2023)
Memorizing the Quran is an activity that is considered sacred and important in religious practice for Muslims. For adults, memorizing the Quran is often a challenge of its own due to time constraints and various other responsibilities. As a student whose average age is twenty years and over, there are difficulties in memorizing, this study aims to analyze whether these five methods are effective for students to use in memorizing verses of the Quran. This research uses the method qualitative with a case study approach. Data sources were taken from five informants through in-depth interviews, all informants are active students at Padang State University, Imam Bonjol State Islamic University, Andalas University. Analysis results show that there are five methods of memorizing the Quran that students can use to memorize verses of the Quran. The five methods are: Wahdah, Kitabah, Sima'i,  Jama' and Talaqqi. Research result This can be used as a guide for students who want to start memorizing the Quran.